Immune response to the hepatitis B antigen in the RTS, S/AS01 malaria vaccine, and co-administration with pneumococcal conjugate and rotavirus vaccines in African children: A randomized controlled trial. Issue 6 (3rd June 2018) - Valéa, Innocent; Adjei, Samuel; Usuf, Effua; Traore, Ousmane; Ansong, Daniel; Tinto, Halidou; Owusu Boateng, Harry; Leach, Amanda; Mwinessobaonfou Some, Athanase; Buabeng, Patrick; Vekemans, Johan; Nana, Louis Arnaud; et al.
ABSTRACT: The RTS, S/AS01 malaria vaccine ( Mosquirix ) reduces the incidence of Plasmodium falciparum malaria and is intended for routine administration to infants in Sub-Saharan Africa. We evaluated the immunogenicity and safety of 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV; Synflorix ) and human rotavirus vaccine (HRV; Rotarix ) when co-administered with RTS, S/AS01 (www.clinicaltrials.gov NCT01345240) in African infants. 705 healthy infants aged 8–12 weeks were randomized to receive three doses of either RTS, S/AS01 or licensed hepatitis B (HBV; Engerix B ) vaccine (control) co-administered with diphtheria-tetanus-acellular pertussis- Haemophilus influenzae type-b-conjugate vaccine (DTaP/Hib) and trivalent oral poliovirus vaccine at 8–12-16 weeks of age, because DTaP/Hib was not indicated before 8 weeks of age. The vaccination schedule can still be considered broadly applicable because it was within the age range recommended for EPI vaccination. PHiD-CV or HRV were either administered together with the study vaccines, or after a 2-week interval. Booster doses of PHiD-CV and DTaP/Hib were administered at age 18 months. Non-inferiority of anti-HBV surface antigen antibody seroprotection rates following co-administration with RTS, S/AS01 was demonstrated compared to the control group (primary objective). Pre-specified non-inferiority criteria were reached for PHiD-CV (for 9/10 vaccine serotypes), HRV, and aP antigens co-administered with RTS, S/AS01 as compared to HBV co-administration (secondary objectives). RTS, S/AS01 induced a response to circumsporozoite protein in all groups. Pain and low grade fever were reported more frequently in the PHiD-CV group co-administered with RTS, S/AS01 than PHiD-CV co-administered with HBV. No serious adverse events were considered to be vaccine-related. RTS, S/AS01 co-administered with pediatric vaccines had an acceptable safety profile. Immune responses to RTS, S/AS01 and to co-administered PHiD-CV, pertussis antigens and HRV were satisfactory.